Identification and pathogenicity of Calonectria pseudoreteaudii causing leaf blight of Eucalyptus––a new record for India. (November 2022) - Bose, Ratnaboli; Banerjee, Sabyasachi; Negi, Nitika; Pandey, Amit; Bhandari, Maneesh S.; Pandey, Shailesh
Abstract: Eucalyptus plantations, which form the basis of several wood-based and pulp/paper-based industries in northern India, are seriously threatened by fungal diseases. Symptoms of Calonectria leaf blight disease with 40–100% disease incidence were frequently encountered during recent disease surveys conducted in commercial Eucalyptus nurseries/plantations in northern India. Isolation from the leaf samples with blight symptoms yielded fungal isolates having Calonectria -like morphology. A BLASTn homology search, phylogenetic analysis conducted using the concatenated data set of partial β-tubulin ( tub2 ) and translation elongation factor-1α ( tef1 ) gene regions confirmed the species as Ca. pseudoreteaudii. In detached leaf assays and glasshouse inoculation experiments, Ca. pseudoreteaudii isolates produced leaf blight symptoms similar to those observed during the field surveys. Finally, Koch's postulates were fulfilled by re-isolating the pathogen from the inoculated leaves. This work is the first time to confirm Ca. pseudoreteaudii as an important incitant of a serious leaf blight disease of Eucalyptus in northern India. These results necessitate a selection program to identify resistant Eucalyptus germplasm against Ca. pseudoreteaudii and other probable pathogenic Calonectri a spp. in India in the long-term. Graphical abstract: Image 1 Highlights: This study reports Calonectria pseudoreteaudii as a destructive pathogen of Eucalyptus in the Indian subcontinent for the first time. The pathogen has been identified based on microscopic features, DNA sequence analysis and pathogenicity tests. This is a new taxonomic addition to the diversity of Calonectria fungi in India. This study warrants testing of new Eucalyptus genotypes for disease resistance on an urgent basis.